Quality Is Everything: Volkswagen production facility performs in‐line inspections with the Zeiss AIMax. Issue 4 (1st August 2019) - Unknown
Abstract: The Volkswagen Commercial Vehicles production facility in Września, Poland, that opened in 2016 is special in several different respects: Not only was it completed in record time – just 23 months – but it is also the largest foreign investment in Poland to date and the most advanced factory in the entire VW family. Quality manager Werner Steinert was tasked with acquiring outstanding measuring technology for this production facility, and he decided to implement a visionary approach to measuring technology at the company's site in Poland.